Contribution Model of al-Mas'ūliyyah al-Jinā'iyyah in the Formulation of Criminal Liability in Indonesia’s New Criminal Code - Abdillah, Junaidi; Nurhayati, Tri; Najichah, Najichah; Zohara, Lira; Tholchah, Muchammad (Al-Ahkam, 2024)
The evolution of criminal law in Indonesia reflects a complex interplay between indigenous legal traditions and external influences, including Islamic law. This article examines the contribution model of al-mas'ūliyyah al-jinā'iyyah (criminal liability in Islamic law) to formulating criminal liability in Indonesia’s New Criminal Code (KUHP Baru). The study adopts a qualitative research method, utilizing a comparative legal analysis framework to explore the dialectic between Islamic criminal law and the New Criminal Code. Data sources include classical legal texts, the book of Qur’anic exegesis and Hadith interpretations, legislative documents related to the New Criminal Code, academic literature, legal commentaries, and jurisprudential analyses. Through this method, the study identifies an elegant interplay between the principles of ḍarar (harm) and the fundamental criminal liability provisions in both systems. This study's findings reveal significant similarities and key differences, such as the role of intent, the typology of legal subjects, and the broader scope of liability for corporate crimes under the New Criminal Code (KUHP Baru). This article concludes that the contribution of al-mas'ūliyyah al-jinā'iyyah to the New Criminal Code lies primarily at the level of values while highlighting the potential for further alignment in specific areas.